Response surface methodological approach for inclusion of perfluorocarbon in actinorhodin fermentation medium - Elibol, M (Elsevier Sci Ltd, 2002)
The combined effects of perfluorocarbon and glucose concentrations on actinothodin production by Streptomyces coelicolor A3(2) were studied in a 2-1 bioreactor using response surface methodology. A 2(2) full-factorial central composite design was employed for experimental design and analysis of the results. The optimum PFC and glucose concentrations were found to be 42.7% and 12.25 g/l, respectively. In these conditions, actinorhodin concentration of 60 mg/l with a biomass concentration of 1.9 g/l, a maximum volumetric oxygen uptake rate of 180 mgO(2)/l h and a glucose consumption rate of 0.110 g glucose/l h was attained. These results are in close agreement with the model predictions. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: response surface methodology; perfluorocarbon; oxygen uptake rate; actinorhodin; Streptomyces coelicolor